Hubungan Self Esteem Dengan Kejadian Nomophobia Pada Remaja Awal Di SMP Barunawati 1 Jakarta Barat Tahun 2023 - Kurniawati Kurniawati; Irma Herliana; Saiful Gunardi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The use of smartphones nowadays is increasingly rapid, even teenagers cannot be separated from using these smartphones, but several conditions cause dependence, especially on the internet network, which ultimately gives rise to incidents of nomophobia or conditions of anxiety, fear and even stress and depression in a person, which is caused by the absence of or being away from the internet network on a cellphone and this is considered a modern phobia resulting from individual interactions with information and communication technology, especially smartphones. The aim of this research is to determine the relationship between self-esteem and the incidence of nomophobia in early adolescents at SMP Barunawati 1 Petamburan, West Jakarta. This type of research is non-experimental quantitative research with a cross-sectional approach. Sampling used proportional stratified random sampling and purposive sampling techniques to obtain a sample of 76 students with research instruments in the form of the Rosenberg Self-Esteem Scale (RSES) and Nomophobia Questionnaire (NMP-Q) questionnaires. Data analysis using Pearson Correlation Product Moment. The results of the research showed that the majority of early adolescents had high self-esteem (71.1%), and the majority of early adolescents had moderate nomophobia (65.8%) and there was a relationship between self-esteem and nomophobia in early adolescents at SMP Barunawati 1 Petamburan, West Jakarta and grades. p value 0.000 < 0.05. Based on the results of this research, it is hoped that research sites can provide counseling or health education about the impacts of excessive smartphone use.